Pengaruh Terapi Kognitif terhadap Penurunan Tingkat Halusinasi - Ikhsan, Muhamad Arif; Suara, Mahyar (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Mental health is still a significant health problem in the world, including in Indonesia. According to WHO (2019) the prevalence of schizophrenia patients is 20 million people in the world. Mental disorder is a disease that tends to become chronic and is often accompanied by a decrease in function (disability) in the field of work, social relations and the ability to care for oneself so that it tends to depend as an aspect of life on the surrounding environment. Based on data from the results of a withdrawal study conducted by researchers at RSJ Islam Kelender in the last 3 years in 2020 there were 18 schizophrenic patients with GSP:Hallucinations, in 2021 there were 20 schizophrenic patients with GSP:Hallucinations and in 2022 until now there are 21 schizophrenic patients with GSP:Hallucinations. To determine the effect cognitive therapy for reducing the level of hallucinations. This research is an analytic research, meaning a study that aims to see a relationship or influence in the form of experimental research using the cross-sectional method, namely the type of dependent variable (dependent) and independent variable (Independent) measured in time the same as using the T-test. There is an effect on the level of hallucinations in schizophrenic patients with hallucinations after being given cognitive therapy Keywords: Hallucinations, Cognitive Therapy (2018-2021)  ABSTRAK Kesehatan jiwa masih menjadi salah satu permasalahan kesehatan yang signifikan di dunia, termasuk di Indonesia. Menurut WHO (2019) bahwa prevlansi pasien Skizofrenian 20 juta orang di dunia. Gangguan jiwa merupakan salah satu penyakit yang mempunyai kecenderungan untuk menjadi kronis dan sering disertai dengan adanya penurunan fungsi (disability) dibidang pekerjaan, hubungan sosial dan kemampuan merawat diri sehingga cenderung menggantungkan sebagai aspek kehidupannya pada lingkungan sekitar, Berdasarkan data hasil study pendahuluan yang dilakukan oleh peneliti di RSJ Islam Kelender dalam 3 tahun terakhir pada tahun 2020 terdapat 18 pasien skizofrenia dengan GSP:Halusinasi, pada tahun 2021 terdapat 20 pasien skizofrenia  dengan GSP:Halusinasi dan pada tahun 2022 sampai sekarang terdapat 21 pasien skizofrenia dengan GSP:Halusinasi. Untuk mengetahui pengaruh terapi kognitif terhadap penurunan tingkat halusinasi. Penelitian ini merupakan penelitian yang bersifat analitik artinya suatu penelitian yang bertujuan untuk melihat adanya hubungan atau pengaruh  dalam bentuk penelitian eksperimen menggunakan metode crossectional yaitu jenis variabel terikat (dependen)  maupun variabel  bebas ( Independen ) diukur dalam waktu yang bersamaan dengan menggunakan uji T-test. Ada pengaruh pada tingkat halusinasi pasien skizofrenia dengan halusinasi setelah diberikan terapi kognitif Kata Kunci: Halusinasi, Terapi Kognitif (2018-2021)